Manajemen Logistik Obat di Instalasi Farmasi RSUD Waibakul Kabupaten Sumba Tengah - Gracewati Rambu Ladu Day; Muntasir Muntasir; Rina Waty Sirait (Media Kesehatan Masyarakat, 2020)
Drug logistics management in the hospital consists of the stages of selection, planning, procurement, acceptance, storage, distribution, destruction, and control, and administration, which must be well-coordinated to function. This study was to determine the description of drug logistics management in the Pharmacy Installation of Waibakul Hospital, Central Sumba Regency. The method used in this research was qualitative. Data were collected by interviews. The results of the study explained that the management of drug logistics at the Waibakul Hospital Pharmacy Installation was already running according to Pharmaceutical Service Standards in Hospitals in Permenkes No.72 of 2016, but it was ineffective as obstacles were identified in each management stage. Constraints in planning were insufficient budget, frequent changes of doctors, and the ineffective use of consumption methods. In procurement, the budget was still lacking, procurement team was not from the hospital and the issue of internet networks in Waibakul Regional Hospital. In admissions, lack of human resources, and drug arrival time over the office hours, lack of infrastructure supporting drug storage such as cabinets, refrigerators, AC, pallets, trolleys, and printers, and medicine warehouse. The study also found the lack of human resources in pharmaceutical warehouses and drug distribution. In the extermination stage, no room was available for storing expired drugs and damaged drugs, and the time for drug culling was longer leading to an accumulation of medical waste.